Time-motion analysis of elite field hockey, with special reference to repeated-sprint activity - Spencer, M.; Lawrence, S.; Rechichi, C.; Bishop, D.; Dawson, B.; Goodman, C. (Journal of Sports Sciences, 2004)
Limited information exists about the movement patterns of field-hockey players, especially during elite competition. Time-motion analysis was used to document the movement patterns during an international field-hockey game. In addition, the movement patterns of repeated-sprint activity were investigated, as repeated-sprint ability is considered to be an important fitness component of team-sport performance. Fourteen members of the Australian men's field-hockey team (age 26±3 years, body mass 76.7±5.6?kg, &Vdot;O2max 57.9±3.6?ml?·?kg-1?·?min-1; mean±s) were filmed during an international game and their movement patterns were analysed. The majority of the total player game time was spent in the low-intensity motions of walking, jogging and standing (46.5±8.1, 40.5±7.0 and 7.4±0.9%, respectively). In comparison, the proportions of time spent in striding and sprinting were 4.1±1.1 and 1.5±0.6%, respectively. Our criteria for `repeated-sprint` activity (defined as a minimum of three sprints, with mean recovery duration between sprints of less than 21?s) was met on 17 occasions during the game (total for all players), with a mean 4±1 sprints per bout. On average, 95% of the recovery during the repeated-sprint bouts was of an active nature. In summary, the results suggest that the motion activities of an elite field-hockey competition are similar to those of elite soccer, rugby and Australian Rules football. In addition, the investigation of repeated-sprint activity during competition has provided additional information about the unique physiological demands of elite field-hockey performance.